THE EVOLUTION OF THE AFROCOLOMBIAN SOCIAL MOVEMENT - Zelinka, Yhara Patricia (Cuadernos de Literatura del Caribe e Hispanoamérica, 2009)
Este artículo propone una reseña histórica del Movimiento Social Afro-Colombiano desde la Colonia hasta hoy, partiendo de las resistencias de los esclavizados y pasando por los palenques y la importancia de la asociación negro-indígena en su lucha por la defensa de territorios y en contra de la marginalización; en este recorrido se exalta el papel de la mujer. El texto también explora cómo la etnoeducación surge como respuesta a la opresión, el silenciamiento cultural y a la desigualdad en que viven las comunidades negras en Colombia y su importancia en la evolución del Movimiento Social Afro-colombiano. PALABRAS CLAVES Cautivo, Palenque, cimarrones, resistencia, etnoeducación, movimiento feminista, multiculturalismo, etnodesarrollo, relaciones interculturales, identidad, Cátedra de Estudios Afro-Colombiano ABSTRACT This paper** traces the evolution of the Afro-Colombian Social Movement from colonial times, starting with a historical background of the early black resistance against slavery: how the first runaway captives formed new societies or communities called palenques. Additionally, this article highlights the importance of the black-indigenous association in defending land and fighting against marginalization, and the role of women in the same context. The Afro-Colombian Social Movement grew out of the oppression and inequality that black communities faced. In the struggle for equal rights, etnoeducación, a new teaching and learning process, was approved by law in the early nineties and is crucial to the evolution of the Afro-Colombian Social Movement. KEY WORDS Captive, Palenque, maroons, etnoeducación (ethnic education), feminist movement, multiculturalism, etnodesarrollo (ethnic development), cross cultural relations, identity, Afro-Colombian studies.